Model Autonomy of Self-Finance Management for Primary Health Care to Enhance Workers’ Satisfaction - Alamin, Ahmad Jet; Issac, Ossama; Teo, Lina; Adyas, Atikah (UI Scholars Hub, 2022)
This study aimed to find an appropriate model of autonomous self-finance management in primary health care (PHC) to enhance workers' satisfaction. This was a cross-sectional study in which data were collected through self-administered questionnaires from 204 workers in ten Regional Public Service Agency for Primary Health Care (RPSAPHC)/Badan Layanan Umum Daerah Pusat Kesehatan Masyarakat (BLUD Puskesmas) in Tangerang District, Banten Province, Indonesia using the partial least squares and structural equation model (PLS-SEM). A total of 73 indicators were used to examine the PHC transformation process to enhance workers' satisfaction. The indicators were grouped into three variables depending on workers' satisfaction: intrinsic, extrinsic, and general satisfaction. In addition, there were five independent variables: financial accountability, generating income, structuring human resources, increasing service quality, and consumer satisfaction. Model autonomy was reflected by all the indicators (cross-loading > 0.70, Cronbach’s alpha > 0.70, average variance extracted > 0.5) affecting workers’ satisfaction (path coefficient = 0.196, p-value = 0.002). The management should apply five indicators (financial accountability, increasing income, structuring human resources, improving service quality, and customer satisfaction) affecting workers' satisfaction to transform the PHC.